2015
DOI: 10.1039/c5ay00150a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and salt-assisted liquid–liquid extraction as an efficient method for natural product extraction

Abstract: A simple, rapid and efficient ultrasound and salt-assisted liquid-liquid extraction (USALLE) method coupled with high-performance liquid chromatography (HPLC) has been introduced for extraction, clean-up and pre-concentration of oleuropein from olive leaves as a model analyte. In this technique, the plant sample was transferred into the extraction solvent (consisting of phosphate buffer and miscible organic solvents) and the mixture was exposed to ultrasonic waves. After ultrasonic-assisted extraction (UAE), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…1 Other works also show that the most efficient ultrasound duration in UALLE is in the range of 1-30 minutes and longer duration may damage the analyte structure. 9 As a rule, extraction efficiency of alkaline drugs is optimized at alkaline pH 3 and we also observed that increasing alkaline pH from 8 to 10 led to increasing efficiency of extraction and the best result was obtained at pH of 10. Other studies on urine 3 and whole blood 10 also showed that pH of 10 is best for methadone extraction because at this pH the drug is in its molecular form.…”
Section: Resultsmentioning
confidence: 72%
“…1 Other works also show that the most efficient ultrasound duration in UALLE is in the range of 1-30 minutes and longer duration may damage the analyte structure. 9 As a rule, extraction efficiency of alkaline drugs is optimized at alkaline pH 3 and we also observed that increasing alkaline pH from 8 to 10 led to increasing efficiency of extraction and the best result was obtained at pH of 10. Other studies on urine 3 and whole blood 10 also showed that pH of 10 is best for methadone extraction because at this pH the drug is in its molecular form.…”
Section: Resultsmentioning
confidence: 72%
“…According to previous reports sodium chloride was selected as a suitable salt for the salting‐out step. The effect of salt concentration in the range of 10–40% w/v was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic‐assisted extraction (UAE) is an ecofriendly, economical and efficient extraction technology . Compared to traditional and other modern extraction means, for example, microwave‐assisted extraction, heating and chemical solvent extraction, UAE reduces the extraction time, lowers the extraction temperature, reduces energy input, and enhances the solubility and experimental reproducibility …”
Section: Introductionmentioning
confidence: 99%